Mathematical Analysis of Bioelectric Potentials - Sunnatova Dilfuza Abatovna,; Tursunova Zuxra Botirovna,; Ismatova Moxiraxon Abror qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Bioelectric potentials are essential electrical signals generated by the movement of ions across cellular membranes, playing a vital role in physiological functions such as nerve conduction, muscle contraction, and cardiac activity. This paper presents a mathematical analysis of bioelectric potentials, focusing on key models like the Hodgkin-Huxley model and the bidomain framework. Through differential equations and computational simulations, the study explores the mechanisms of signal generation and propagation in biological tissues. The findings highlight the importance of mathematical modeling in understanding bioelectric phenomena and their applications in biomedical engineering and clinical diagnostics.